2016
DOI: 10.1080/14786419.2016.1258557
|View full text |Cite
|
Sign up to set email alerts
|

A new oleanolic-type triterpene glycoside fromAnchusa italica

Abstract: A new oleanolic-type triterpene glycoside, (3β,21β)-21-[(β-d-glucopyranosyl-(1→2)-β-d-glucopyranosyl)oxy]-3-hydroxyolean-12-en-28-oic acid (1), together with five analogues, oleanazuroside 1 (2), oleanazuroside 2 (3), 24-hydroxytormentic acid ester glucoside (4), 24-epi-pinfaensin (5), and oleanolic acid 3-O-α-l-arabinoside (6) were isolated from the n-butyl alcohol extract of Anchusa italica. Their structures were determined spectroscopically and compared with previously reported spectral data. Compounds 3-4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 20 publications
1
5
0
Order By: Relevance
“…The tri-glycosylated compound 20 and 25 presented a similar glycosylation, with the presence of a glucuronic methyl ester group, observed for the first time in the study of Cartabia et al [ 14 ]. The ability of A. officinalis to produce saponins was already reported in previous studies [ 31 , 38 , 50 ] and their strong accumulation in shoot parts of mycorrhized A. officinalis is in line with the study by Cartabia et al [ 14 ].…”
Section: Discussionsupporting
confidence: 88%
“…The tri-glycosylated compound 20 and 25 presented a similar glycosylation, with the presence of a glucuronic methyl ester group, observed for the first time in the study of Cartabia et al [ 14 ]. The ability of A. officinalis to produce saponins was already reported in previous studies [ 31 , 38 , 50 ] and their strong accumulation in shoot parts of mycorrhized A. officinalis is in line with the study by Cartabia et al [ 14 ].…”
Section: Discussionsupporting
confidence: 88%
“…Their content is influenced by various biotic stimuli, such as herbivory and pest attack or related to plant-microorganism symbiosis (Hussain et al, 2017 ). Interestingly, the ability to produce these compounds has been already reported for Anchusa spp., specifically oleanane-type glycosidic derivatives mainly present in the foliar part of the plants (Koz et al, 2009 ; Chen et al, 2017 ). In our analysis, and in opposition to phenolic compounds, saponins 17, 32, 33, and 34 showed maximum accumulation in M shoots, with a fold change increment ranking from 1.73 to 2.26.…”
Section: Discussionmentioning
confidence: 99%
“…Plants are an important source of phenolic compounds, which are known for their antibacterial properties and can have applications as natural preservatives either in the food field or in the cosmetic field [4,[12][13][14]. Previous chemical studies have shown that Anchusa italic Retz is rich in polyphenols, flavonoids, saponins, tannins, vitamin E [15][16][17][18]. The seeds of the plant are rich in saturated fatty acids, unsaturated fatty acids, and alkaloids [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%